Pre and protohistoric stone architectures : comparisons of the social and technical contexts associated to their building : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France). - Cousseau, Florian,; Laporte, Luc, (Archaeopress Archaeology, 2020)
Proceedings, with full text in English and French, from session XXXII-3 of the XVIII UISPP World Congress, Paris, 2018. The volume aims to break the usual limits on the fields of study and to deconstruct some preconceived ideas.